Knowledge of symptoms and risk factors of breast cancer among women: a community based study in a low socio-economic area of Mumbai, India - Ranjan Kumar Prusty; Shahina Begum; Anushree Patil; D. D. Naik; Sharmila Pimple; Gauravi Mishra (BMC, 2020)
Abstract Background Breast cancer (BC) is leading cancer among women in India accounting for 27% of all cancers among women. Factors that make the policymakers and public health system worried are rising incidence of breast cancer in India and more importantly high death rates among breast cancer patients. One of the leading causes of high breast cancer deaths is lack of awareness and screening leading to the late presentation at an advanced stage. Therefore, the current research aimed to understand the knowledge of breast cancer symptoms and risk factors among women in a low socio-economic area of Mumbai. Methods A cross-sectional study was conducted at Prabhadevi, Mumbai and primary data was collected from 480 women aged 18-55 years. Structured questionnaire was used to collect quantitative data pertaining to awareness, signs and symptoms of breast cancer. Bivariate and multivariate regression techniques were used for understanding of the socio-demographic differentials in breast cancer awareness among women. Results The study found that around half (49%) of the women were aware of breast cancer. The women who were aware of breast cancer considered lump in breast (75%), change in shape and size of breast (57%), lump under armpit (56%), pain in one breast (56%) as the important and common symptoms. Less than one-fifth of the women who were aware of breast cancer reported early menstruation (5.6%), late menopause (10%), hormone therapy (13%), late pregnancy (15%) and obesity (19%) as the risk factors for breast cancer. The multivariate regression analysis showed women who had more than 10 years of schooling (Adjusted Odds Ratio: 3.93, CI: 2.57-6.02, P < 0.01) were about 4 times more likely to be aware of breast cancer than women who had less than 10 years of schooling. Conclusion In conclusion, knowledge of danger signs and risk factors of breast cancer were low among women in the community. This may lead to late detection of breast cancer among women in the community. Therefore, the study calls for advocacy and larger intervention to enhance knowledge of breast cancer among women in the particular region with a special reference to women with low education.